PROGRAM MENGOPTIMALKAN PELAYANAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA KHATULISTIWA KOTA PONTIANAK - Fauzi Ahmad E.21110047 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This articel  was “implementation program to optimalized service from water company in Pontianak City”. This articel was intended to describe and analyze the factors of   implementation program optimalization service from water company in Pontianak City  that has not been done properly.The conclusion of this research is less maximum of implementation program optimalitation service from water company in Pontianak city ,specialed in west Pontianak distric city., it was influenced by several factors. The first factor was, lack of communication like less of socialization that cause less understanding from public and customers  to  program optimalitation and  problems about optimalitation service from public water company in Pontianak city. Second, the resource factor in this matter was lack of adequate facilities in implementation program optimalitation service that truly influence it. Third, the perceived attitude of the implementor much less support in the implementation of the program that cause it not running optimally. Fourth, bureaucratic structures that involving many peoples and customers cause the  implementation program optimalitation takes long times to process. Keyword : Implementation of optimalization program, communication factors, resource factors, disposition factors, and bureaucratic structure factors.